Implementation of the "Some" Communication Model on Social Media Marketing of Bayukarta Karawang Hospital - Ekawati, Dian; Fransiska , Tria Maria (Journal La Medihealtico, 2023)
As the current hospital in Indonesia has shifted toward profit oriented, one of the causes is that Indonesia's entry into a free-market system that requires us to change our perspective on hospitals, (manajemen.net, 26th June 2020). As the age and technology developed, social media is considered to be an effective and efficient marketing medium for hospitals. Social media is one of the few that make it easier for people to get information on things because social media is easily accessible to all. The purpose of this research is to learn about Bayukarta's hospital marketing strategies through social media of Instagram. The research used concept theory "The Circular Model of SOME" (share, optimize, manage, engage) by Regina Luttrell. Methods used case research with qualitative descriptive approaches and data-collection techniques with interviews, observations. As a result of this research, Bayukarta's hospital chose social media Instagram towards increasingly growing social media users and matched Bayukarta's hospital target market. Bayukarta Hospital's Marketing propagates information about products or services offered to audiences through a post on the social media account Instagram @rs.bayukarta, before posting content done by collecting photos of products or services, events, promotions and discounts. The social instagram of bayukarta hospital is staffed by social media admins to respond to individual comments or questions of followers. To build a trust in Bayukarta Hospital consumers involves competent medical professionals and health-care professionals.